Transformation, adaptation and universalism. Issue 1 (2nd January 2017) - Andrews,
Abstract : A reply to:Heatley, Brian. 2017. "Paris: optimism, pessimism and realism." Global Discourse . 7 (1): 10–22. http://dx.doi.org/10.1080/23269995.2017.1300402